On Quasi S-Propermutable Subgroups of Finite Groups. (1st August 2020) - Yang, Hong; Mahboob, Abid; Zafer, Asim; Ali, Iftikhar; Ullah, Zafar; Haq, Absar Ul
Abstract : A subgroup H of a finite group G is said to be quasi S -propermutable in G if K ⊲ ¯ G such that H K is S -permutable in G and H   ∩   K ≤ H q s G, where H q s G is the subgroup formed by all those subgroups of H which are S -propermutable in G . In this paper, we give some generalizations of finite group G by using the properties and effects of quasi S -propermutable subgroups.